GUGATAN WARGA NEGARA SEBAGAI MEKANISME PEMENUHAN HAK ASASI MANUSIA DAN HAK KONSTITUSIONAL WARGA NEGARA - Abdul Fatah (Universitas Airlangga, 2013)
The purpose of the state law (rule of law) is to protect the rights and freedoms of human citizens to realize the general welfare, of the actions that an arbitrary ruler. It required strict regulation in order to protect citizens from becoming victims of arbitrariness state officials or authorities. A mechanism to protect the citizen right from abuse of power by government is through citizen lawsuit. However currently literature of citizen lawsuit is a weak in Indonesia, hence there should have been writing that discussion issues of citizen lawsuit from theory side. Keywords: Rule of law, Human Rights, Government